ANALISIS PENGENDALIAN KUALITAS DAN EFEKTIVITAS DENGAN INTEGRASI KONSEP FAILURE MODE & EFFECT ANALYSIS DAN FAULT TREE ANALYSIS SERTA OVERALL EQUIPMENT EFFECTIVENESS - Susetyo, Joko (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
Effective measurement with Overall Equipment Effectiveness (OEE) method and concept of Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) is hoped able to in crease production volume and quality. OEE method is based on three factors, they are: availability, performance and quality. OEE value is got by multiplying the three factors. FMEA concept is carried out to decide the critical rating, evidence, and defection rating. RPN calculation is the result of those three rating multiplication shows the risk level of a failure. FTA concept is carried out by using OR gate to know the probability of failure evidence. The analysis that is got show OEE value of Paper Machine in two year: first year 60%, in crease to 83% in the second year. Cutter Asahi’s OEE value, in the first year, is 67%, in the second year become 73%. The first cause of low OEE is PLN drop power energy. The FMEA result identification is got highest RPN value that is 245 at Paper Machine process, with failure mode dirty, the main cause is dirt that dissolved in its production process and the screen that does not work maximally. To handle that cause needs a routine checking and cleaning in the process and screen by Paper Machine operator. Identification result of FTA indicates that highest failure probability on Paper Machine part is 0.01145.